Persepsi Mahasiswa Peserta Merdeka Belajar Kampus Merdeka Universitas Andalas terhadap Perkembangan Soft Skills - Dyne Soraya Lathifah; Nur Afrainin Syah; Abdiana Abdiana; Dian Pertiwi; Fitratul Ilahi (Universitas Palan, 2026)
Merdeka Belajar Kampus Merdeka (MBKM) is a new policy that aims to improve student’s soft skills and hard skills before entering the workforce. The purpose of this study was to explore the perceptions od Universitas Andalas students participating in MBKM on the development of soft skills. This research was conducted using qualitative research methods with grounded theory design. The sampling technique used purposive sampling and obtained 18 informants from 14 faculties at Universitas Andalas. Data were obtained through focus group discussions with informants who had signed an informed consent sheet. The results showed that the perceptions of students who participated in MBKM activities could develop student’s soft skills. Merdeka Belajar Kampus Merdeka program has a positive impact on improving the ability of solve problems, critical thinking, communication, team work, creativity, time management, and leadership. Obstacles that students get when participating in MBKM activities and can hinder the development of soft skills include information discrepancies, difficulty converting credits, lack of socialization to students, unsynchronized technical guidelines, and limited use of language.